ส่วนประสมการตลาดบริการที่มีผลต่อผู้ประกอบการในจังหวัดสมุทรสาคร ต่อการเลือกสํานักงานบัญชี - ปัทมา อุบล (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
The objective of this independent study was to study services marketing mix affecting enterprises in Samut Sakhon province towards selecting accounting service firms. Samples of this study were specified to 400 entrepreneurs or decision makers with the authority to select accounting service firms for their business, registered with the Bureau of Business Development in Samut Sakhon as the corporate business, located in Samut Sakhon province. Questionnaire was used to gather data in according to convenient sampling method and the data was then analyzed using descriptive statistic, including frequency, percentage and mean. The results of the study showed that most respondents owned the printing business with company limited registration. Total number of permanent workforce working in their business was 51-100 persons. Amount of business registered capital was 1-5 million Bath. Length of business operation was 10 years or more. Regarding the study on the use of services from accounting service firms, the findings presented that the respondents mostly took audit service. In average, they paid for the service fee to the accounting service firm at the amount of 10,000 Baht or more per month. The location of account service firms where they took services was in Bangkok. Source of information influencing their decision making to select accounting service firm was self-decision. Reason of receiving services from accounting service firms was referred to the need of services being offered by professionals.